2019
DOI: 10.1002/hep.30761
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4 Inhibition as a Therapeutic Target for Alcoholic Liver Disease: From Bedside to Bench

Abstract: Alcoholic liver disease (ALD) is a major cause of liver‐related mortality. There is still no US Food and Drug Administration–approved therapy for ALD, and therefore, identifying therapeutic targets is needed. Our previous work demonstrated that ethanol exposure leads to up‐regulation of cAMP‐degrading phosphodiesterase 4 (PDE4) expression, which compromises normal cAMP signaling in monocytes/macrophages and hepatocytes. This effect of ethanol on cAMP signaling contributes to dysregulated inflammatory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 45 publications
4
45
2
Order By: Relevance
“…We used a PDE4-specific inhibitor as well as Pde4b knockout mice and showed that the ethanol-mediated decrease in CPT1A expression was prevented via the PPARα/PGC1α/SIRT1 pathway in an in vivo mouse model of chronic Liber deCarli feeding for four weeks [ 111 ]. Recently, we recapitulated the same results in a chronic ethanol binge (10 plus one, NIAAA) model [ 112 ]. Moreover, a single administration of PDE4 inhibitor prevented the ethanol-mediated decrease in cAMP levels and attenuated liver injury.…”
Section: Camp Signaling In Aldsupporting
confidence: 58%
See 4 more Smart Citations
“…We used a PDE4-specific inhibitor as well as Pde4b knockout mice and showed that the ethanol-mediated decrease in CPT1A expression was prevented via the PPARα/PGC1α/SIRT1 pathway in an in vivo mouse model of chronic Liber deCarli feeding for four weeks [ 111 ]. Recently, we recapitulated the same results in a chronic ethanol binge (10 plus one, NIAAA) model [ 112 ]. Moreover, a single administration of PDE4 inhibitor prevented the ethanol-mediated decrease in cAMP levels and attenuated liver injury.…”
Section: Camp Signaling In Aldsupporting
confidence: 58%
“…In this study, the effect of ethanol on hepatocyte and liver cAMP levels was not evaluated. Later, work from our group showed that chronic ethanol feeding significantly decreased cAMP levels in mouse livers as well as in hepatocytes isolated from ethanol-fed mice [ 111 , 112 ]. However, the relative decrease was larger in the whole liver.…”
Section: Camp Signaling In Aldmentioning
confidence: 99%
See 3 more Smart Citations